Students’ Speaking Ability in Interpreting Something (a case study of using Indonesian Language - Tsamratul’aeni Tsamratul’aeni (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2023)
This study intends to convey the ability to interpret and speak especially early childhood in certain areas in Palopo using qualitative research. The instrument in this study was a standard Indonesian speaking test by interview directly. The results found were quite surprising because not all children were able to speak in a standard manner, some of them were influenced by local language even though the messages they conveyed were understood by the researcher well, but it was undeniable that some were also difficult to understand. This study also illustrates that the relationship between children's interpretation ability and speaking ability is related to one another, but in this case the researcher does not see one side only in the sense that it includes the strengths and weaknesses of each child.